Comparison of open abdominal hysterectomy and total laparoscopic hysterectomy: a study in a teaching hospital - Sridhar, M.; Susmitha, Chillamherla (International Surgery Journal, 2016)
Background: Abdominal and vaginal hysterectomies were the most common type of surgeries till the advent of laparoscopic surgery. , we compared the open abdominal hysterectomy to the total laparoscopic hysterectomy in this prospective randomized study. Methods: 157 women aged between 35 – 75 years who were diagnosed with abnormal bleeding, enlarged uterus, endometrial carcinoma, sarcoma or hyperplasia and posted for hysterectomy were included into the study. The patients were assigned into 2 groups based on the clinical presentation. Group ABH consisted of patients undergoing open abdominal hysterectomy and Group TLH consisted of patients undergoing total laparoscopic hysterectomy. Results: The average time for operation for total laparoscopic hysterectomy and abdominal hysterectomy was 109 minutes and 123 minutes respectively. The blood loss was significantly more in abdominal surgery of over 200ml to that of about 55ml in laparoscopic surgery as was the duration of hospital stay of the patients. The prevalence of complications was 34.9% in the ABH Group and 21.1% in the TLH group. Conclusions: Laparoscopic hysterectomy was better than open abdominal hysterectomy with respect to lesser hospital stay, blood loss and number of complications. Although the procedural cots are higher, the duration of hospital stay and the lesser complications compensates the expense and makes the procedure comparable to the abdominal procedure.